1978
DOI: 10.1111/j.1469-8749.1978.tb15205.x
|View full text |Cite
|
Sign up to set email alerts
|

Maximal Aerobic Capacity of Young People with Spastic Cerebral Palsy

Abstract: SUMMARY Maximal aerobic capacity in bicycle ergometer tests was studied in nine children (aged 11 to 12 years) and five young men (aged 19 to 23 years), all with a spastic form of cerebral palsy, and compared with non‐handicapped control groups. Results showed somewhat lower values for heart rate, oxygen uptake/kg, ventilation/kg and blood lactate concentrations for the majority of the spastic group. The physical work capacity of the handicapped group amounted to about 50 per cent of the corresponding values f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0
1

Year Published

1983
1983
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(34 citation statements)
references
References 8 publications
4
29
0
1
Order By: Relevance
“…[1][2][3][4] These poor fitness levels have been well documented by means of exercise tests. Moreover, exercise testing has been used as a primary outcome measure of therapy and exercise programmes in children and adolescents with CP.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] These poor fitness levels have been well documented by means of exercise tests. Moreover, exercise testing has been used as a primary outcome measure of therapy and exercise programmes in children and adolescents with CP.…”
Section: Discussionmentioning
confidence: 99%
“…Aerobic fitness of children or athletes with cerebral palsy has been vigorously investigated by Bar-Or 10) , Fernandez et al 23,24) , Lundberg 25,26) , Maltais et al [27][28][29][30] , van den Berg-Emons et al [31][32][33][34] , and other researchers since the 1960s. These studies were based on work physiology that was mainly established by Åstrand et al 9) .…”
Section: History Of Research On Aerobic Fitness In Individuals With Cmentioning
confidence: 99%
“…These included several empirical studies, most of which have been forgotten. However, some work physiology concerning this particular field of rehabilitation has survived because these studies provided insights into the improvement of residual function (i.e., aerobic fitness) in children or athletes with cerebral palsy rather than the recovery of lost function 3,10,[25][26][27][28] . However, only a few recent studies by researchers like Nieuwenhuijsen et al 55,56) and Satonaka, et al [19][20][21][22] have reported on nonathletic adults with cerebral palsy rated to GMFCS level III or IV.…”
Section: History Of Research On Aerobic Fitness In Individuals With Cmentioning
confidence: 99%
See 2 more Smart Citations